THU0004 A de novo non-sense erap1 polymorphism in two hla-b*27-negative twins with axial spondyloarthritis. (12th June 2018) - Padula, M.C.; Martelli, G.; Giuzio, R.; Amato, C.; Carbone, T.; Gilio, M.; Leccese, P.; Tramontano, G.; Padula, A.A.; D'Angelo, S.
Abstract : Background: Axial spondyloarthritis (axSpA) is a group of inflammatory disorders primarily affecting the spine that includes ankylosing spondylitis (AS) and non-radiographic axSpA. AS is strongly associated with HLA-B*27. A small percentage of HLA-B*27-positive subjects develop AS, suggesting the role of other genes in AS susceptibility. 1, 2 Among these genes, ERAP1 acts as "molecular ruler". It encodes the endoplasmic reticulum aminopeptidase 1 protein, responsible for the peptides trimming for the efficient binding to class I major histocompatibility complex (MHC). Several common gene SNPs (single nucleotide polymorphisms) were associated with the susceptibility to AS, but the presence of other ERAP1 polymorphisms was supposed to explain the genotype-phenotype correlation. 1, 3, 4 Objectives: The aim of this study is to genotype the ERAP1 gene whole structure searching for common and additional polymorphisms in two HLA-B*27-negative twins. Methods: We integrated a bioinformatics and a second level molecular approach in order to characterise ERAP1 gene. Specific primer pairs were designed for the coverage of all gene regions. Genomic DNA was isolated from the whole blood of two 36 years-old axSpA male twins. They are HLA-B*27-negative (HLA-A*02, HLA-A*32; HLA-B*07; HLA-CW*07). The coexistence of Crohn's disease (CD) was documented in both patients after the initial diagnosis of axSpA. Primer-specific polymerase chain reaction (PCR) was carried out. PCR products were sequenced and bioinformatics tools (BlastN and Mutation Surveyor) were queried for the mutational analysis. Phyre2 on line software was used for predicting the protein tertiary structure. Results: Molecular characterisation of ERAP1 gene identified a de novo homozygous guanine to adenine substitution at 15 132 position of exon 2 nucleotide sequence (NG_027839.1:g.15312G>A). This substitution is a stop-codon variation that directly generates an early premature termination codons (PTC). The 3D model of the protein showed a significant difference of the folding when wild-type and mutant protein were compared. The non-sense transcript could result in the production of a truncated protein, formed by 30 amino acids (NP_001035548.1:p.Trp31Ter) (figure 1). Conclusions: A de novo stop-codon ERAP1 variant was identified for the first time in axSpA. We suggest that the PTC-related ERAP1 protein could contribute to AS risk by affecting the protein role. References: [1] Robinson PC and Brown MA. Molecular Immunology2014;57:2–11. [2] Akkoç N, et al. Curr Rheumatol Rep. 2017;19(5):26. [3] Wang X, et al. Mol Med Rep. 2017;16(5):6532–6543. [4] Roberts AR, et al. Proc Natl Acad Sci USA2017;114(3):558–561. Acknowledgements: Thanks to Professor Ignazio Olivieri to have conveyed us the importance of honesty and humility, to teach us the enthusiasm of knowing and doing. Disclosure of Interest: None declared